Tìm x,biết:
a, x.(x−2)+x−2=0
b, 5x.(x−3)−x+3=0
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a: Ta có: \(x\left(x-3\right)-x^2+5=0\)
\(\Leftrightarrow-3x+5=0\)
hay \(x=\dfrac{5}{3}\)
b: Ta có: \(x^2-6x=0\)
\(\Leftrightarrow x\left(x-6\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}x=0\\x=6\end{matrix}\right.\)
a. x(x-2)+x-2=0
=> (x-2).(x+1)=0
=> x-2=0 hoặc x+1=0
=> x=2 hoặc x=-1
b. 5x(x-3)-x+3=0
=> 5x(x-3)-(x-3)=0
=> (x-3).(5x-1)=0
=> x-3=0 hoặc 5x-1=0
=> x=3 hoặc x=1/5
a) \(x\left(x-2\right)+x-2=0\)
<=> \(\left(x-2\right)\left(x+1\right)=0\)
<=> \(\orbr{\begin{cases}x-2=0\\x+1=0\end{cases}}\)
<=> \(\orbr{\begin{cases}x=2\\x=-1\end{cases}}\)
Vậy...
b) \(5x\left(x-3\right)-x+3=0\)
<=> \(\left(x-3\right)\left(5x-1\right)=0\)
<=> \(\orbr{\begin{cases}x-3=0\\5x-1=0\end{cases}}\)
<=> \(\orbr{\begin{cases}x=3\\x=\frac{1}{5}\end{cases}}\)
Vậy...
\(a,\Leftrightarrow x\left(x+5\right)=0\Leftrightarrow\left[{}\begin{matrix}x=0\\x=-5\end{matrix}\right.\\ b,\Leftrightarrow3x\left(x-1\right)+\left(x-1\right)=0\\ \Leftrightarrow\left(x-1\right)\left(3x+1\right)=0\\ \Leftrightarrow\left[{}\begin{matrix}x=1\\x=-\dfrac{1}{3}\end{matrix}\right.\\ c,\Leftrightarrow\left(x+2\right)\left(2x-3\right)=0\Leftrightarrow\left[{}\begin{matrix}x=-2\\x=\dfrac{3}{2}\end{matrix}\right.\)
`@` `\text {Ans}`
`\downarrow`
`a,`
`(x - 2)(x - 3) =0`
`<=>`\(\left[{}\begin{matrix}x-2=0\\x-3=0\end{matrix}\right.\)
`<=>`\(\left[{}\begin{matrix}x=0+2\\x=0+3\end{matrix}\right.\)
`<=>`\(\left[{}\begin{matrix}x=2\\x=3\end{matrix}\right.\)
Vậy, `S = {2; 3}`
`b,`
`x^2 - 5x = 0`
`<=> x(x - 5) = 0`
`<=>`\(\left[{}\begin{matrix}x=0\\x-5=0\end{matrix}\right.\)
`<=>`\(\left[{}\begin{matrix}x=0\\x=0+5\end{matrix}\right.\)
`<=>`\(\left[{}\begin{matrix}x=0\\x=5\end{matrix}\right.\)
Vậy, `S = {0; 5}`
`c,`
`x^2 - 9 = 0`
`<=> x^2 = 0 + 9`
`<=> x^2 = 9`
`<=> x^2 = (+-3)^2`
`<=> x = +-3`
Vậy, `S = {3; -3}`
`d,`
`4x^2 - 25 = 0`
`<=> 4x^2 = 25`
`<=> x^2 = 25/4`
`<=> x^2 = (+-5/2)^2`
`<=> x = +-5/2`
Vậy,` S = {5/2; -5/2}.`
a: =>x-2=0 hoặc x-3=0
=>x=2 hoặc x=3
b: =>x(x-5)=0
=>x=0 hoặc x=5
c: =>(x-3)(x+3)=0
=>x=3 hoặc x=-3
d: =>(2x-5)(2x+5)=0
=>x=5/2 hoặc x=-5/2
a) x(x - 2) + x - 2 = 0
(x - 2)(x + 1) = 0
Hoặc x - 2 = 0 => x = 2
Hoặc x + 1 = 0 => x = -1
Vậy x = -1; x = 2.
b) 5x(x - 3) - x + 3 = 0
5x(x - 3) - (x - 3) = 0
(x - 3)(5x - 1) = 0
Hoặc x - 3 = 0 => x = 3
Hoặc 5x - 1 = 0 => x = 1/5.
Vậy x = 1/5; x = 3.
Ta có:
a) \(x\left(x-2\right)+x-2=0\)
\(\Rightarrow x\left(x-2\right)+\left(x-2\right)=0\)
\(\Rightarrow\left(x+1\right)\left(x-2\right)=0\)
\(\Rightarrow\hept{\begin{cases}x+1=0\\x-2=0\end{cases}}\)
\(\Rightarrow\hept{\begin{cases}x=-1\\x=2\end{cases}}\)
b) \(5x\left(x-3\right)-x+3=0\)
\(\Rightarrow5x\left(x-3\right)-\left(x-3\right)=0\)
\(\Rightarrow\left(5x-1\right)\left(x-3\right)=0\)
\(\Rightarrow\hept{\begin{cases}5x-1=0\\x-3=0\end{cases}}\)
\(\Rightarrow\hept{\begin{cases}x=\frac{1}{5}\\x=3\end{cases}}\)
a) x ( x - 2 ) + x - 2 = 0
x ( x - 2 ) + ( x - 2 ) . 1 = 0
( x - 2 ) ( x + 1 ) = 0
\(\Rightarrow\orbr{\begin{cases}x-2=0\\x+1=0\end{cases}}\Rightarrow\orbr{\begin{cases}x=2\\x=-1\end{cases}}\)
Vậy x = 2 ; x = -1
b) 5x ( x - 3 ) - x + 3 = 0
5x ( x - 3 ) - ( x - 3 ) . 1 = 0
( x - 3 ) ( 5x - 1 ) = 0
\(\Rightarrow\orbr{\begin{cases}x-3=0\\5x-1=0\end{cases}}\Rightarrow\orbr{\begin{cases}x=3\\5x=1\end{cases}}\Rightarrow\orbr{\begin{cases}x=3\\x=\frac{1}{5}\end{cases}}\)
Vậy x = 3 ; x = 1/5
a/ \(x\left(x-2\right)+x-2=0\)
\(\Leftrightarrow\left(x-2\right)\left(x+1\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}x-2=0\\x+1=0\end{matrix}\right.\)
\(\Leftrightarrow\left[{}\begin{matrix}x=2\\x=-1\end{matrix}\right.\)
Vậy ...
b/ \(5x\left(x-3\right)-x+3=0\)
\(\Leftrightarrow\left(5x-1\right)\left(x-3\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}5x-1=0\\x-3=0\end{matrix}\right.\)
\(\Leftrightarrow\left[{}\begin{matrix}x=\dfrac{1}{5}\\x=3\end{matrix}\right.\)
Vậy ..
a. x.(x - 2) + x - 2 = 0
\(\Leftrightarrow\)x(x-2)+(x-2)=0
\(^{_{ }\Leftrightarrow}\)(x-2)(x+1)=0
\(\left[{}\begin{matrix}x-2=0\\x+1=0\end{matrix}\right.\Leftrightarrow\)\(\left[{}\begin{matrix}x=2\\x=-1\end{matrix}\right.\)
Vậy x\(\in\)\(\left\{2;-1\right\}\)
b. 5x(x-3)-(x+3)
\(^{_{ }\Leftrightarrow}\)5x(x-3) + (x-3) = 0
\(^{_{ }\Leftrightarrow}\)(x-3)(5x+1) = 0
\(\Rightarrow\)\(\left\{{}\begin{matrix}x-3=0\\5x+1=0\end{matrix}\right.\)\(\Rightarrow\)\(\left\{{}\begin{matrix}x=3\\x=\dfrac{-1}{5}\end{matrix}\right.\)
Vậy...